Wireless connection of bioimpedance measurement circuits based-on AD5933: A state of the art - Dell'osa, Antonio Héctor (2021)
This contribution describes the state of the art in bioimpedance measurements through development boards to build portable devices that perform in-situ measurements and potential technological opportunities to separate the AD5933 integrated circuit from a PC. The presented research is based on prototypes developed with the aim of achieving portability with the AD5933 integrated circuit and it includes different wireless connection methods and a varied software design for the acquisition, visualization and storage of data obtained from biological systems. As a result, this work describes twenty articles that perform wireless connectivity using different microprocessors for different applications. These references seek to explore technological trends, deficiencies, and opportunities for future development projects in telemedicine.